Quark masses and mixings in minimally parameterized UV completions of the Standard Model - Alkofer, Reinhard; Eichhorn, Astrid; Held, Aaron; Nieto, Carlos M.; Percacci, Roberto; Schröfl, Markus (Annals of physics, 2020)
We explore a simple parameterization of new physics that results in an ultraviolet complete gauge-quark sector of the Standard Model. Specifically, we add an antiscreening contribution to the beta functions of the gauge couplings and a flavor-independent, antiscreening contribution to the beta functions of the Yukawa couplings. These two free parameters give rise to an intricate web of Renormalization Group fixed points. Their predictive power extends to the flavor structure and mixing patterns, which we investigate to demonstrate that some of the free parameters of the Standard Model could be determined by the Renormalization Group flow.